Critical Analysis of Children's Legal Skills in the Hanafi Mazhab - Andi Wijaya; Siti Nurhaliza (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2021)
This research explores the concept of legal proficiency or